2022
DOI: 10.14309/ajg.0000000000001742
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Comorbidities on Follow-up Colonoscopy After Positive Colorectal Cancer Screening Results: A Population-Based Cohort Study

Abstract: INTRODUCTION: Fecal occult blood tests (FOBTs) are colorectal cancer screening tests used to identify individuals requiring further investigation with colonoscopy. Delayed colonoscopy after positive FOBT (FOBT1) is associated with poorer cancer outcomes. We assessed the effect of comorbidity on colonoscopy receipt within 12 months after FOBT1. METHODS:Population-based healthcare databases from Ontario, Canada, were linked to assemble a cohort of 50-74-year-old individuals with FOBT1 results between 2008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…Consistent with earlier research, we found that high physical comorbidity burden was associated with prolonged diagnostic intervals, lower odds of fast-track referrals and endoscopy, and higher odds of emergency presentation . While patients with MHM have been found to have higher comorbidity, our study findings suggest that MHM and physical comorbidities are independently associated with timely cancer investigations.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with earlier research, we found that high physical comorbidity burden was associated with prolonged diagnostic intervals, lower odds of fast-track referrals and endoscopy, and higher odds of emergency presentation . While patients with MHM have been found to have higher comorbidity, our study findings suggest that MHM and physical comorbidities are independently associated with timely cancer investigations.…”
Section: Discussionsupporting
confidence: 90%
“…IBS may provide an alternative explanation for cancer-delaying referrals in some patients, with longer symptom to diagnosis intervals and a higher emergency diagnosis risk, as observed in our study and previous studies. 8,27 Consistent with earlier research, we found that high physical comorbidity burden was associated with prolonged diagnostic intervals, 7,8 lower odds of fast-track referrals 29 and endoscopy, 3,19 and higher odds of emergency presentation. 19 While patients with MHM have been found to have higher comorbidity, 16 our study findings suggest that MHM and physical comorbidities are independently associated with timely cancer investigations.…”
Section: Interpretation In Contextsupporting
confidence: 89%
See 3 more Smart Citations